EFFICACY OF TUBERCULOSIS CASES DETECTION AMONG THE POPULATION OF DUSHANBE IN THE REPUBLIC OF TAJIKISTAN - S.P. ALIEV; O.I. BOBO KHODZHAEV; I.S. MAKHMUDZODA; F.O. MIRZOEVA; L.SH. UKUMA TSHOEVA; S.R. MIRZOEVA (Avicenna Tajik State Medical University, 2018)
Objective: Study of the effectiveness of identifying persons with suspected tuberculosis (TB) and verification of their diagnosis among the population of Dushanbe, the Republic of Tajikistan Methods: This study includes data from an active screening of 676815 persons who applied for various reasons to primary health care (PHC) facilities in Dushanbe for the period 2011-2015, which underwent a full clinical, x-ray and laboratory examination. Results: When conducting the active screening of persons who applied to institutions in a PHC facility in Dushanbe, 15645 patients with various clinical forms of TB were identified within 5 years. Of these, 14159 patients with pulmonary TB (90.5%) were identified, 11327 (80.0%) of whom suffered from a pulmonary form with a bacteria excretion, 22832 (20.0%) - a pulmonary form without a bacteria excretion and 1486 (9.5% ) - extrapulmonary TB. At the same time, in 1283 cases (8.2%) of the total number of patients, multidrug resistance was established, and in 92 (0.6%) patients - a combination of active TB with HIV infection. Conclusion: The findings show that providing access to active screening and rapid diagnostic methods helps to improve the detection rates for new TB cases.